Audiological Abnormalities in Vitiligo Patients: A Hospital-Based Cross-Sectional Study - Prabha,Neel (2020)
Abstract Introduction There are some discrepancies in the literature about the influence of vitiligo on auditory functions. According to some authors, vitiligo influences hearing, whereas others question such influence. Therefore, we conducted a study to evaluate audiological functions in vitiligo patients. Objectives To determine the effect of vitiligo on auditory functions. Methods A hospital-based observational study was done from January 2017 to July 2017. Clinically diagnosed cases of vitiligo were enrolled for the study. A complete otological examination was conducted in all patients. Results Fifty-two patients (male: female 28:24) were included in the study. Ten patients (19.2%) had sensorineural hearing loss (SNHL). Seven patients (13.5%) had bilateral and 3 (5.7%) had unilateral SNHL. High frequency loss was seen in 17 out of 20 ears (10 affected patients), 6 ears had both low and high-frequency hearing loss. Of 12 ears with speech frequency involvement, mild hearing loss was seen in 5 and moderate to severe in 1 ear.Most cases of SNHL were detected in the age group 41 to 60 years old (63.6%), which was statistically significant (p-value 0.00). Conclusion The results of this study suggest that vitiligo patients require routine monitoring for auditory functions for early identification of SNHL. Older subjects with vitiligo might be at a higher risk for audiological abnormalities. These patients should also be informed regarding the associated risk with noise and ototoxic drug exposure.